Analysis of stress tolerance, competitive-anxiety, heart rate variability and salivary cortisol during successive matches in male futsal players - Bruno Laerte Lopes Ribeiro; Nicole Leite Galvão-Coelho; Raíssa Nóbrega Almeida; Gustavo Zampier dos Santos Lima; Leonardo de Sousa Fortes; Arnaldo Luis Mortatti (BMC Sports Science, Medicine and Rehabilitation, 2022)
Abstract Background This study aimed to compare the stress tolerance, competitive anxiety, heart rate variability and salivary cortisol before and during successive futsal competitive matches (3 matches in 4 days) in young male futsal players. Methods 10 young male futsal players (16.9 ± 0.7 age; 71.0 ± 5.1 kg; 174.9 ± 4.3 cm) were monitored during one training session and across a competitive period with 3 successive matches. External load was determined by the PlayerLoad method, while session rating of perceived exertion was used to calculate the internal training and competitive load. The stress tolerance was examined using Daily Analysis of Life Demand in Athletes questionnaire and the Competitive State Anxiety Inventory was used to analyze the competitive anxiety. The Time and frequency monitoring parameters were used to analyze the vagal cardiac autonomic marker. sC was analyzed using enzyme-linked immunosorbent assay. Results A generalized estimating equation showed a significant difference for PlayerLoad from M1 to TS, M2 and M3, from M2 to M3 (p < 0.05), and for session rating of perceived exertion from M1 to Ts and M3 (p < 0.05). A difference for sources [χ2 (3) = 1.481, p = 0.68] or symptoms [χ2 (3) = 3.893, p = 0.27] was not found. There was no significant difference in any of the competitive anxiety [cognitive anxiety (F (1.644; 14.799) = 4.6, p = 0.73, ŋ2 p = 0.28), somatic anxiety (F (2,09; 18,85) = 26.07 p = 0.057; ŋ2 p = 0.27) or self-confidence (F(2.07; 18.85) = 15.875 p = 0.152; ŋ2 p = 0.18)] domains. The HRV parameters (time domain and frequency) and Salivary Cortisol (sC) (χ2 (3) = 4.320 p = 0.229) did not significantly change during the successive matches. Conclusion The competitive scenario in which the players were evaluated did not significantly modify the stress tolerance, or the athletes’ state of anxiety, which in turn was not able to promote changes in the cardiac vagal modulation or in the sC levels before the matches.